School Psychology Unified Call for Deeper Understanding, Solidarity, and Action to Eradicate Anti-AAAPI Racism and Violence. Issue 2 (3rd July 2021) - Truong, Dieu M.; Tanaka, Marie L.; Cooper, Jennifer M.; Song, Sam; Talapatra, Devadrita; Arora, Prena; Fenning, Pamela; McKenney, Elizabeth; Williams, Stacy; Stratton-Gadke, Kasee; Jimerson, Shane R.; Pandes-Carter, Lauren; et al.
Abstract: Racist rhetoric blaming the Asian, Asian American, and Pacific Islander (AAAPI) community for the COVID-19 pandemic has precipitated a surge of violence against the AAAPI community in the United States, including the Atlanta mass shooting on March 16, 2021. These incidents resurfaced the ongoing racism against AAAPIs that has largely been unaddressed despite lasting almost 2 centuries. The erasure of AAAPIs' historical oppression, unique cultures, languages, immigration experiences, and contributions to scientific and social justice advancement in the United States has hindered AAAPI voices from being heard. School psychologists are ethically bound to promote equity and dismantle racism; it is imperative to increase visibility of AAAPIs' experiences across training levels (P–12 and graduate programs), settings, and systems. In this unified statement, school psychology organizations have come together to reaffirm the field's commitment to anti-racism by offering proactive strategies to effectively promote visibility and equity for AAAPI students, families, and communities. Impact Statement Although there has been a complete absence of discussion of anti-AAAPI racism and anti-racism in school psychology, the field is actively committed to dismantling systemic racism and inequalities in P–12 schools, institutions of higher education, and communities across our nation. This statements seeks to address this absence by providing (a) a much-needed starting point for school psychologists to learn about the history of discrimination, racism, and violence targeting AAAPIs in the United States that has been virtually unaddressed; (b) a critical context for the recent rise in COVID-19-related anti-AAAPI violence while shedding critical light on the deep-seated racism that has oppressed AAAPIs for centuries in America; and (c) beginning strategies that school psychology faculty members, practitioners, and students can engage in to dismantle anti-AAAPI racism across individual and systems levels.